1, 2, 3-Triazole pharmacophore-based benzofused nitrogen/sulfur heterocycles with potential anti-Moraxella catarrhalis activity. Issue 23 (1st December 2015) - Maračić, Silvija; Kraljević, Tatjana Gazivoda; Paljetak, Hana Čipčić; Perić, Mihaela; Matijašić, Mario; Verbanac, Donatella; Cetina, Mario; Raić-Malić, Silvana
Graphical abstract: Abstract: Versatile 1, 2, 3-triazole pharmacophore-based benzofused heterocycles containing halogen-substituted aromatic (9 –17 and25 –28 ), 7-substituted coumarin (18 –23 and29 –30 ) or penciclovir-like subunit (31a, b –38a ) were designed and synthesized to evaluate their antibacterial activities against selected Gram-positive and Gram-negative bacteria. Hybridization approach using environmentally friendly Cu(I)-catalyzed click reaction under microwave irradiation was adopted in the synthesis of regioselective 1, 4-disubstituted 1, 2, 3-triazole tethered heterocycles (9 –23 and25 –30 ), while post-N-alkylation of NH -1, 2, 3-triazoles afforded both 2, 4- (31a –38a ) and 1, 4-disubstituted (31b –33b, 35b –37b ) 1, 2, 3-triazole regioisomers. The compounds18 –23 and25 –30 revealed fluorescence in the violet region of the visible spectrum with a strong influence of phenyl spacer in25 –30 on both wavelength and emission intensity. Fusion of selected subunits led to new hybrid architecture, benzothiazole–1, 2, 3-triazole–coumarin29 that demonstrated extremely narrow spectrum activity towards fastidious Gram-negative bacteria Moraxella catarrhalis. Selected hybrid showed the potency against Moraxella catarrhalis (MIC ⩽ 0.25 μg/mL) comparable to that of reference antibiotic azithromycin, which suggested that further investigations are necessary to optimize this potential hit compound as a new anti- Moraxella catarrhalis agent.